2021
DOI: 10.3390/ani11071892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Egg Laying on Feather and Plasma Corticosterone Concentrations in Turkey (Meleagris gallopavo) Hens

Abstract: Phenological differences in energy demand (i.e., reproductive status) might influence the measurement of corticosterone. The objective of this study was to compare corticosterone concentrations in feathers (FCORT) and plasma (PCORT) for turkey hens before and during egg laying. Secondary feathers 1 and 3, and a plasma sample were collected from 50 hens at 30 weeks (before egg laying) from two purebred lines. The hens were reexamined during lay (45 weeks) to collect regrown feathers and plasma samples. Corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The reason may be related to an inherently large variation in feather CORT concentrations of poultry ( Weimer et al, 2018 ). In particular, the variation in MC treatment was greater than in NC treatment, which appears to be reasonable because of the greater individual variation in feather CORT accumulation rate of hens exposed to stress conditions than normal conditions ( Leishman et al, 2021 ). In addition, it should be noted that feather CORT concentrations in laying hens may also vary with stage and extent of feather growth because growing feathers are more responsive to changes in blood CORT levels than full-grown and inert feathers ( Bortolotti et al, 2008 ; Lattin et al, 2011 ; Jenni-Eiermann et al, 2015 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The reason may be related to an inherently large variation in feather CORT concentrations of poultry ( Weimer et al, 2018 ). In particular, the variation in MC treatment was greater than in NC treatment, which appears to be reasonable because of the greater individual variation in feather CORT accumulation rate of hens exposed to stress conditions than normal conditions ( Leishman et al, 2021 ). In addition, it should be noted that feather CORT concentrations in laying hens may also vary with stage and extent of feather growth because growing feathers are more responsive to changes in blood CORT levels than full-grown and inert feathers ( Bortolotti et al, 2008 ; Lattin et al, 2011 ; Jenni-Eiermann et al, 2015 ).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, our observation is also likely related to the general physiology of laying hens. Leishman et al (2021) reported that a female-line turkey had greater feather CORT concentrations than a male-line turkey. Bortolotti et al (2008) also reported that the feather CORT concentrations were highly and positively correlated to the number of laying eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that FCORT levels differ between different turkey genetic lines which may indicate underlying genetic differences 29,30 . Heritability of FCORT or fault bars has yet to be estimated; however, several estimates exist for plasma corticosterone in various domestic and wild bird species.…”
mentioning
confidence: 96%